The species composition of dragonfly in UiTM Negeri Sembilan / Siti Nur Faizura Junaidi - Junaidi, Siti Nur Faizura (2016)
This study were about to record the composition and determine the diversity of dragonfly in UiTM Negeri Sembilan. Since, there was no checklist have been documented yet. Four different sites has been chosen named as site A (building block area), site B (pond area near to forest reserve), site C (pond area near to open field area) and site D (pond area surrounded by open field area). Insect net has been used for collecting the dragonflies then, the pinning and identification have been conducted by using standard method. One family have been found is Libellulidae and 9 genera were listed as followed Crocothemis, Brachythemis, Diplacodes, Orthetrum, Neurothemis, Pantala, Acisoma, Macrodiplax, and Lathrecista. There were 6 individuals from 3 genera was recorded at site A, 28 individuals from 7 genera at site B, while 58 individuals from 7 genera at site C and 25 individuals from 5 genera were found at site D. By using Shannon-Wiener diversity index, site B had shown the highest diversity (H’= 1.77), followed by site D (H’= 1.49), next by site C (H’=1.46) and the least was at site A (H’=1.09). For Margalef richness index, site B (R=1.80) had the highest value, followed by site C (R=1.48), site D (R=1.24) and the least site A (R=1.12). Meanwhile, for evenness index, site A (E=1.00) have the highest value and been followed by site D (E=0.93), site B (E=0.91) and the least value at site C (E=0.75). In conclusion, the species composition and diversity of dragonflies in UiTM Negeri Sembilan were successfully identified and recorded.